The impacts of public hospital comprehensive reform policies on hospital medicine cost, revenues and healthcare expenditures 2014–2019: An analysis of 103 tertiary public hospitals in China - Pan, Lin; Xiao, Kai; Zhu, Huanhuan; Luo, Li (Frontiers in Health Services, 2023)
Objective To explore the impact of implementation of the comprehensive public hospital reform policy (CPHRP) on medicine costs, revenues and medical expenditures in tertiary public hospitals in China. Methods The data of this study was collected from local administrations to obtain operational data of healthcare institutions and medicine procurement data for 103 tertiary public hospitals from 2014 to 2019. The propensity matching score method and the difference-in-difference method were used jointly to assess the impact of reform policies on tertiary public hospitals. Results After the implementation of the policy, drug revenue in the intervention group decreased by ¥ 86.3 million (p = 0.076) compared to the control group; medical service revenue increased by ¥ 108.5 million (p < 0.001); government financial subsidies increased by ¥ 20.3 million (p = 0.085); the average medicine cost per outpatient and emergency visit decreased by ¥ 15.2 (p = 0.062); the average medicine cost per hospitalization decreased by ¥ 504 (p = 0.040); however, the medicine cost decreased by ¥ 38.2 million (p = 0.351), the average cost per visit for outpatient and emergency decreased by ¥ 0.562 (p = 0.966), the average cost per hospitalization decreased by ¥ 152 (p = 0.844), which are not significant. Conclusions The implementation of reform policies has changed the revenue structure of public hospitals; the proportion of drug revenue decreased, while the proportion of service income increased, especially in service income and government subsidies. Meanwhile, the average medicine cost of outpatient, emergency, and inpatient visits per time were all reduced, which played a certain role in reducing the disease burden of patients.